Analisis Hubungan Perceived Quality dan Brand Awareness terhadap Brand Loyalty melalui Brand Image pada Produk Jamu Melydel - Siti Tasyakurotul Mubarokah; Syariefful Ikhwan; Slamet Bambang Riono; Dumadi Dumadi; Andi Yulianto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The Indonesian herbal medicine industry faces major challenges in building sustainable consumer loyalty amid intense competition with modern health products. The main issue lies in the relatively weak brand image and limited competitiveness in terms of packaging, pricing, and product quality consistency, which have prevented consumer loyalty from being fully achieved. This study aims to analyze the influence of perceived quality and brand awareness on brand loyalty through brand image in the case of Jamu Melydel. The research employed a quantitative approach with a descriptive design. The study population consisted of Jamu Melydel customers, with 202 respondents selected using a non-probability sampling technique. Data were collected through observation, questionnaires, and documentation, and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results show that perceived quality has a positive and significant effect on brand image, and brand awareness also has a positive and significant effect on brand image. However, brand image does not significantly affect brand loyalty, while perceived quality also fails to directly influence brand loyalty. In contrast, brand awareness has a positive and significant impact on brand loyalty. Furthermore, brand image does not mediate the relationship between perceived quality or brand awareness and brand loyalty. These findings suggest that brand awareness is the key factor in shaping consumer loyalty toward Jamu Melydel, while brand image and perceived quality remain insufficient to sustain loyalty. The implications of this study highlight the need to strengthen brand awareness strategies, improve brand image, and foster product innovation to enhance the competitiveness of the traditional herbal medicine industry.